The Existence of the Papuan People's Assembly in Special Autonomy: A Comparative Legal Study Between Indonesia and France - Redemptus Denaryo; Khiswatul Barokah; Gladysta Viola Serafim; Sabrina Amaliya Lutfiana; Riana Susmayanti (Universitas Negeri Surabaya, 2025)
Article 18B paragraph (1) of the 1945 Constitution provides an explanation regarding the birth of an asymmetrical decentralization policy or the granting of special autonomy to a region in Indonesia. This special autonomy is given to several regions in Indonesia, one of which is Papua through Law Number 21 of 2001 concerning Special Autonomy for Papua Province. In carrying out the implementation of special autonomy in Papua, the Papua People's Assembly (MRP) was formed which is a cultural representation of indigenous Papuans as regulated in PP No. 64 of 2008 concerning MRP. In this case, there are many challenges faced by the MRP to foster justice for the Papuan people. This research is a type of normative juridical research with statutory, comparative law, and case approach methods. Primary, secondary, and tertiary legal materials are analyzed using systematic interpretation techniques. Based on the results of the research, to solve the existing problems, a legal comparison can be made with the French state which also provides special autonomy to the New Caledonia region which has a representative institution such as the MRP.